CHEMICAL CONTROL OF SOYBEAN POWDERY MILDEW - TOIGO, Sonia; SANTOS, Idalmir dos; CARNIELETTO, Carlos Eduardo; MAZZARO, Sérgio Miguel (Scientia Agraria, 2008)
The occurrence of powdery mildew in soybean, especially when the environment conditions are favorable to disease development, can affect the crop and cause significant grain yield damages. In order to evaluate the effectiveness of fungicides to control powdery mildew (Microsphaera diffusa) in soybean (Glycine max), an experiment was carried out in the city of Pato Branco, PR, during the 2004/2005 cropping season, using soybean cultivar EMBRAPA 48. The products were applied once, when the plants were at the R1 developmental stage. Severity of the disease was evaluated immediately before the application and weekly thereafter. The area under the disease progress curve (AUDPC) was determined based on data obtained for the various treatments. The treatments consisted of the following active principles: azoxystrobin + cyproconazole, flutriafol + methyl thyophanate, cyproconazole + propiconazole, fenarimol, flutriafol, trifloxistrobina + cyproconazole, trifloxystrobin + tebuconazole, and tetraconazole. A control treatment without application of fungicides was included as well. The highest AUDPC value was observed in the control, at 51.8%. The fungicide treatments with the lowest AUDPC values, providing the best soybean productivity increases were flutriafol + methyl thyophanate, trifloxystrobin + tebuconazole, and trifloxystrobin + cyproconazole, providing disease control percentages of 85.8, 82.1 e 90.3% respectively. Grain yield increase was influenced by the fungicides. By comparison against the yield obtained in the control, the estimated yield increase range provided by the fungicides was between 33.2% and 51%.